Comparative study of social networks in post-socialist Western Balkan countries. Formal and informal networking for information diffusion - Emelj Tuna, Natalija Bogdanov, Aleksandra Nikolic, Ana Simonovska (Eastern European Countryside, 2020)
Rural areas in the Western Balkan are faced with severe socio-economic and political challenges. Among many other, these include lack of access to knowledge and information as well as scepticism about formal forms of cooperation. Yet, the evidence on social capital and network structures' influence on the access of rural population to information and knowledge in these countries is still sparse, even though this can be one of the most influential factors shaping rural development. In this paper a multi-country comparison was applied so to provide empirical evidence of the existing level of social capital structures (networks) in North Macedonia, Serbia and Bosnia and Herzegovina. The conducted analyses indicate that even with the low participation rates, all farmers, both members and non-members of organisations, perceive membership in formal organisations as useful. Additionally, the results support the presumption that even sparse informal networks, mostly built on strong personal ties, are more effective channels for information transfer in absence of efficient/active formalized types of cooperation. This implies that rural development policy measures have to be crafted in a way to transform farmers from passive subjects into creative actors, particularly in sharing and promoting good practices.
Keywords: social capital, rural development, transition, Western Balkan.